Computer Modeling Explains the Structural Reasons for the Difference in Reactivity of Amine Transaminases Regarding Prochiral Methylketones - Teixeira, Iris S. [UNESP]; Farias, André B.; Horta, Bruno A. C.; Milagre, Humberto M. S. [UNESP]; de Souza, Rodrigo O. M. A.; Bornscheuer, Uwe T.; Milagre, Cintia D. F. [UNESP] (MDPI, 2022)
Amine transaminases (ATAs) are pyridoxal-5′-phosphate (PLP)-dependent enzymes that catalyze the transfer of an amino group from an amino donor to an aldehyde and/or ketone. In the past decade, the enzymatic reductive amination of prochiral ketones catalyzed by ATAs has attracted the attention of researchers, and more traditional chemical routes were replaced by enzymatic ones in industrial manufacturing. In the present work, the influence of the presence of an α,β-unsaturated system in a methylketone model substrate was investigated, using a set of five wild-type ATAs, the (R)-selective from Aspergillus terreus (Atr-TA) and Mycobacterium vanbaalenii (Mva-TA), the (S)-selective from Chromobacterium violaceum (Cvi-TA), Ruegeria pomeroyi (Rpo-TA), V. fluvialis (Vfl-TA) and an engineered variant of V. fluvialis (ATA-256 from Codexis). The high conversion rate (80 to 99%) and optical purity (78 to 99% ee) of both (R)-and (S)-ATAs for the substrate 1-phenyl-3-butanone, using isopropylamine (IPA) as an amino donor, were observed. However, the double bond in the α,β-position of 4-phenylbut-3-en-2-one dramatically reduced wild-type ATA reactivity, leading to conversions of <10% (without affecting the enantioselectivity). In contrast, the commercially engineered V. fluvialis variant, ATA-256, still enabled an 87% conversion, yielding a corresponding amine with >99% ee. Computational docking simulations showed the differences in orientation and intermolecular interactions in the active sites, providing insights to rationalize the observed experimental results.
Keywords: Amine transaminase; Biocatalysis; Chiral amines